Power and Ideology in Online News: A Sociology-Cognitive Critical Discourse Analysis of Misty Copeland’s Representation in CNN - Ratna Dewi; Jumino Suhadi; Devi Pratiwy (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2025)
This study examines how power and ideology operate in CNN’s online news representation of Misty Copeland, using Teun A. van Dijk’s Socio-Cognitive Critical Discourse Analysis (SCA) framework. The research explores how linguistic choices and discursive strategies simultaneously empower and constrain the portrayal of race, gender, and success within liberal media narratives. Data were drawn from selected CNN articles covering Copeland’s achievements and analyzed through textual, cognitive, and social dimensions to reveal how language, cognition, and ideology interact in shaping media representation. The findings indicate that CNN constructs Copeland’s identity through a discourse of “contained empowerment,” which outwardly celebrates diversity while subtly reproducing liberal and post-feminist ideologies. Linguistically, terms such as “trailblazer,” “breaking barriers,” and “making history” elevate Copeland as an exceptional figure. Cognitively, these expressions activate shared mental models grounded in meritocracy, reinforcing beliefs that upward mobility stems primarily from individual effort. Ideologically, the coverage depoliticizes issues of race and gender by transforming structural inequalities into narratives of personal perseverance. The study concludes that CNN’s portrayal of Copeland naturalizes inequality through celebratory empowerment discourse. While promoting diversity, the narrative obscures institutional power and social asymmetry. This research contributes to Critical Discourse Studies by integrating socio-cognitive and intersectional perspectives, highlighting the need for critical media literacy in understanding how digital news both emancipates and regulates meaning in contemporary culture.